Positive electrode for power storage device, and power storage device
Patent Information
- Application Number
- JP2023128555
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0011】 本発明によれば、曲げ負荷に起因する正極活物質層の割れを抑制できる。
Smart Images

Figure 2025024445000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode for an electricity storage device, and to an electricity storage device. [Background technology]
[0002] Patent Document 1 discloses a flat-type electric storage device constructed by stacking a plurality of electric storage cells in series. The electric storage cell includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The positive electrode has a positive electrode active material layer formed on one side of a foil-shaped positive electrode current collector. The negative electrode has a negative electrode active material layer formed on one side of a foil-shaped negative electrode current collector, and is disposed so that the negative electrode active material layer faces the positive electrode active material layer of the positive electrode. The electric storage device disclosed in Patent Document 1 is formed by stacking a plurality of the above electric storage cells so that the positive electrode current collector and the negative electrode current collector are in contact with each other.
[0003] Patent Document 2 discloses a method for continuously manufacturing electrodes using a roll. The electrode manufacturing method disclosed in Patent Document 2 includes a coating step and a drying step. The coating step is a step of coating an electrode mixture containing an active material, a solvent, etc., onto a current collector sent out from a feed roll. The drying step is a step of drying the coating layer of the electrode mixture applied to the current collector after the coating step. The current collector after the drying step is wound up on a winding roll. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-16825 A [Patent Document 2] Japanese Patent Application Publication No. 11-102696 Summary of the Invention [Problem to be solved by the invention]
[0005] As a method for increasing the energy density of a power storage cell, it is possible to apply a configuration in which the basis weight of the active material layer is increased and a configuration in which the content of the active material in the active material layer is increased. However, when both of the above configurations are applied to a positive electrode having a structure in which an active material layer is provided on the surface of a current collector, a problem occurs in that the active material layer is easily detached from the current collector during the manufacture of a power storage device using the positive electrode.
[0006] As a result of intensive research by the present inventors, it was found that the cause of the detachment of the active material layer is the bending load applied to the active material layer during or after the manufacture of the positive electrode. In other words, the flexibility of the active material layer decreases with an increase in the basis weight of the active material layer and an increase in the content of the active material in the active material. As a result, when a bending load is applied to the active material layer, the active material layer cannot withstand the bending load and cracks occur in the active material layer. Due to the cracks in the active material layer, the active material layer is easily detached from the current collector during the manufacture of the electricity storage device.
[0007] During or after the production of the positive electrode, a bending load is applied to the active material layer when, for example, the current collector passes through a guide roll for changing the transport direction, and when the current collector is wound around a winding roll, causing the current collector to bend along the outer periphery of the roll. [Means for solving the problem]
[0008] The positive electrode for an electricity storage device that solves the above problems comprises a current collector having a first surface, and a positive electrode active material layer formed on the first surface of the current collector, the positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing charge carriers, and the positive electrode active material layer has a basis weight of 50 mg / cm. 2 and the content of the positive electrode active material in the positive electrode active material layer is 97 mass % or more, and the positive electrode active material layer contains a water-based binder having a glass transition temperature of less than 7°C and single-walled carbon nanotubes.
[0009] The aqueous binder preferably contains a compound having an aromatic ring. The compound having an aromatic ring is preferably a styrene-butadiene rubber. It is preferable that the current collector is a bipolar electrode having a second surface facing opposite to the first surface, and in which the positive electrode active material layer is formed on the first surface of the current collector and a negative electrode active material layer is formed on the second surface.
[0010] The energy storage device that solves the above problem includes a positive electrode having a positive electrode active material layer provided on a first surface of a positive electrode current collector, a negative electrode having a negative electrode active material layer provided on a first surface of a negative electrode current collector, the negative electrode active material layer being arranged so as to face the positive electrode active material layer of the positive electrode, a separator arranged between the positive electrode active material layer and the negative electrode active material layer, and a spacer arranged between first surfaces of the positive electrode current collector and the negative electrode current collector and adhered to the first surfaces of the positive electrode current collector and the negative electrode current collector, wherein the positive electrode is a positive electrode for the above energy storage device. Effect of the Invention
[0011] According to the present invention, cracks in the positive electrode active material layer caused by bending load can be suppressed. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a cross-sectional view of a positive electrode according to the first embodiment. [Diagram 2] FIG. [Diagram 3] FIG. 11 is a cross-sectional view of a bipolar electrode according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. [First embodiment] <Positive electrode> The positive electrode of the first embodiment is used as an electrode of a power storage device. The power storage device is, for example, a secondary battery such as a nickel-metal hydride secondary battery or a lithium-ion secondary battery. The power storage device may also be an electric double layer capacitor. In the following, a case where the positive electrode is an electrode of a lithium-ion secondary battery will be described.
[0014] 1, the positive electrode 21 includes a positive electrode current collector 21a having a first surface 21a1, and a positive electrode active material layer 21b formed on the first surface 21a1 of the positive electrode current collector 21a. In this embodiment, the positive electrode current collector 21a corresponds to the current collector described in the claims.
[0015] [Positive electrode current collector] The positive electrode collector 21a is a chemically inactive electrical conductor for continuously passing a current through the positive electrode active material layer 21b during discharging or charging of the lithium ion secondary battery. The positive electrode collector 21a has a shape that can be bent and deformed into a curved state, for example, a foil shape. The thickness of the foil-shaped positive electrode collector 21a is, for example, 5 μm or more, preferably 10 μm or more. The thickness of the foil-shaped positive electrode collector 21a is, for example, 100 μm or less, preferably 60 μm or less.
[0016] An example of the positive electrode current collector 21a is an aluminum current collector whose surface serving as the first surface 21a1 is made of aluminum. The aluminum current collector may be a single body entirely made of aluminum, or a composite having a portion made of aluminum and a portion made of a material other than aluminum. An example of the single body is aluminum foil. An example of the composite is a multilayer structure in which the layer making up the first surface 21a1 is an aluminum layer, or a substrate whose surface including the first surface 21a1 is coated with an aluminum film.
[0017] The positive electrode current collector 21a may be formed of a material other than aluminum. Examples of materials other than aluminum include metal materials, conductive resin materials, and conductive inorganic materials. Examples of the metal materials include copper, nickel, titanium, and stainless steel (for example, SUS304, SUS316, SUS301, SUS304, etc., as specified in JIS G 4305:2015). Examples of the conductive resin materials include resins in which a conductive filler is added to a conductive polymer material or a non-conductive polymer material as necessary.
[0018] The first surface 21a1 of the positive electrode current collector 21a may be covered with a known protective layer such as a carbon coating layer. The first surface 21a1 of the positive electrode current collector 21a may be treated by a known method such as plating.
[0019] [Cathode active material layer] The positive electrode active material layer 21b is provided on the first surface 21a1 of the positive electrode current collector 21a. The weight of the positive electrode active material layer 21b is 50 mg / cm 2 More than 60 mg / cm 2 More preferably, it is 70 mg / cm or more. 2 That's all. The above weight is 50mg / cm 2 By making the positive electrode 21 exceeding 0.1%, it is possible to effectively increase the energy density of a lithium ion secondary battery using the positive electrode 21. Furthermore, the increase in the energy density of the lithium ion secondary battery improves battery characteristics such as battery capacity and long-term output.
[0020] The weight of the positive electrode active material layer 21b is, for example, 90 mg / cm 2 or less, preferably 80 mg / cm 2 The above weight is 90mg / cm 2 When the thickness of the positive electrode active material layer 21b is set to 50 mg / cm or less, the thickness of the positive electrode active material layer 21b is reduced, and thus the height of the lithium ion secondary battery using the positive electrode 21 can be reduced. 2 That's all.
[0021] The thickness of the positive electrode active material layer 21b is, for example, 200 μm or more and 600 μm or less. The density of the positive electrode active material layer 21b is, for example, 1.5 g / cm 3 or more and 2.5 g / cm 3 or less. Here, the positive electrode active material layer 21b may be subjected to a pressing process. The thickness of the pressed positive electrode active material layer 21b is, for example, 200 μm or more, preferably 240 μm or more. The thickness of the pressed positive electrode active material layer 21b is, for example, 530 μm or less, preferably 470 μm or less. The density of the pressed positive electrode active material layer 21b is, for example, 1.7 g / cm 3 or more and 2.5 g / cm 3 or less.
[0022] The positive electrode active material layer 21b contains a positive electrode active material, a specific positive electrode binder, and single-walled carbon nanotubes. (Positive electrode active material) The positive electrode active material can occlude and release charge carriers such as lithium ions. The positive electrode active material is not particularly limited, and those that can be used as the positive electrode active material of a lithium ion secondary battery are adopted. Examples of the positive electrode active material include polyanion-based compounds having an olivine-type structure, lithium composite metal oxides having a layered rock salt structure, and metal oxides having a spinel structure. The positive electrode active material may be used alone or in combination of multiple types.
[0023] The positive electrode active material is preferably a polyanion-based compound having an olivine-type structure (hereinafter referred to as an olivine-type active material). Examples of the olivine-type active material include compounds represented by the general formula LiM h PO 4 In the general formula LiM h PO 4 M is at least one element selected from the group consisting of Mn, Fe, Co, Ni, Cu, Mg, Zn, V, Ca, Sr, Ba, Ti, Al, Si, B, Te, and Mo, and h is a numerical value satisfying 0 < h < 2. Specific examples of the olivine-type active material include, for example, olivine-type lithium iron phosphate (LiFePO 4) and olivine-type lithium manganese iron phosphate (LiMnFePO 4 ) are mentioned.
[0024] The particle shape of the positive electrode active material is not particularly limited, but is preferably a granule formed by agglomeration of primary particles of the positive electrode active material. By using the granule, the flexibility of the positive electrode active material layer 21b is increased. The particle diameter of the primary particles constituting the granule is, for example, 50 nm or more and 500 nm or less. The particle diameter of the primary particles is determined by small angle X-ray scattering (SAXS). In detail, the particle diameter of the primary particles is a numerical value defined as an average particle diameter (D50) obtained from the particle diameter distribution after determining the particle diameter distribution of the primary particles assuming that the primary particles are spherical. The average particle diameter (D50) of the granule is, for example, 5 μm or more and 15 μm or less. The average particle diameter (D50) of the granule can be measured using a laser diffraction type particle size analyzer.
[0025] The positive electrode active material is preferably a particle having a carbon coating on its surface. In this case, in the positive electrode active material layer 21b, a hydrophobic interaction occurs between the particle surface of the positive electrode active material and the single-walled carbon nanotube. This allows the positive electrode active material and the single-walled carbon nanotube to work together when a bending load is applied to the positive electrode active material layer 21b. A preferred example of the positive electrode active material particle having a carbon coating is a particle having a core composed of a granulated body of an olivine type active material and a carbon coating formed on the surface of the core.
[0026] The content of the positive electrode active material in the positive electrode active material layer 21b is 97% by mass or more, preferably 98% by mass or more, and more preferably 98.5% by mass or more. The content of the positive electrode active material in the positive electrode active material layer 21b is, for example, 99% by mass or less, and preferably 98.8% by mass or less. By making the content of the positive electrode active material 97% by mass or more, it is possible to effectively increase the energy density of the lithium ion secondary battery using the positive electrode 21. Furthermore, by increasing the energy density of the lithium ion secondary battery, battery characteristics such as battery capacity and long-term output are improved.
[0027] (Specific positive electrode binder) The specific positive electrode binder is an aqueous binder having a glass transition temperature of less than 7° C. The aqueous binder is a binder that is used by being mixed with the positive electrode active material in a state where it is dispersed or dissolved in an aqueous solvent.
[0028] The glass transition temperature of the specific positive electrode binder is less than 7° C., preferably 0° C. or less, and more preferably −5° C. or less. When the glass transition temperature of the specific positive electrode binder is less than 7° C., the flexibility of the positive electrode active material layer 21b is improved. The glass transition temperature of the specific positive electrode binder is, for example, −50° C. or more.
[0029] The glass transition temperature is the glass transition onset temperature in a DSC curve measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min. The method for measuring the DSC curve is in accordance with JIS K 7121 (1987), except that the heating rate is 10°C / min. The glass transition onset temperature is the temperature at which the DSC curve begins to change from the low-temperature baseline.
[0030] Examples of the specific positive electrode binder include various resin materials, for example, fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluorine rubber, thermoplastic resins such as polypropylene and polyethylene, imide resins such as polyimide and polyamideimide, alkoxysilyl group-containing resins, acrylic resins such as poly(meth)acrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, alginates such as sodium alginate and ammonium alginate, water-soluble cellulose ester crosslinked bodies, and starch-acrylic acid graft polymers. The specific positive electrode binder contained in the positive electrode active material layer 21b may be one type or two or more types.
[0031] The glass transition temperature of a specific positive electrode binder can be adjusted by changing the degree of polymerization of the resin material and the ratio of the constituent units that make up the resin material. For example, in the case of styrene-butadiene rubber, the glass transition temperature can be adjusted by changing the ratio of the constituent units styrene and butadiene. Specifically, the glass transition temperature of styrene-butadiene rubber can be lowered by increasing the ratio of butadiene to styrene.
[0032] The specific positive electrode binder is preferably a compound having an aromatic ring. In this case, in the positive electrode active material layer 21b, π-π interaction occurs between the aromatic ring of the specific positive electrode binder and the single-walled carbon nanotube. This allows the specific positive electrode binder and the single-walled carbon nanotube to work together when a bending load is applied to the positive electrode active material layer 21b. An example of a compound having an aromatic ring is styrene-butadiene rubber.
[0033] The content of the specific positive electrode binder in the positive electrode active material layer 21b is, for example, 0.8 mass% or more, preferably 0.9 mass% or more, and more preferably 1.0 mass% or more. By increasing the content of the specific positive electrode binder, the binding property in the positive electrode active material layer 21b can be improved.
[0034] The content of the specific positive electrode binder in the positive electrode active material layer 21b is, for example, 2.0 mass % or less, preferably 1.5 mass % or less, and more preferably 1.3 mass % or less. The specific positive electrode binder is a component in the positive electrode active material layer 21b that does not contribute to charging and discharging. By reducing the content of the component that does not contribute to charging and discharging, the energy density of the lithium ion secondary battery can be increased. And, by increasing the energy density of the lithium ion secondary battery, the battery characteristics such as the battery capacity and long-term output can be improved.
[0035] (single-walled carbon nanotubes) Carbon nanotubes can be broadly divided into two types: single-walled carbon nanotubes and multi-walled carbon nanotubes. Single-walled carbon nanotubes are cylindrical bodies formed by rolling up a single graphene sheet seamlessly. In contrast, multi-walled carbon nanotubes are composites in which multiple single-walled carbon nanotubes of different diameters are contained within a single-walled carbon nanotube. As a result, single-walled carbon nanotubes are more flexible than multi-walled carbon nanotubes.
[0036] The positive electrode active material layer 21b contains single-walled carbon nanotubes. In the positive electrode active material layer 21b, the single-walled carbon nanotubes may be present in a state of being bundled with, for example, several tens of single-walled carbon nanotubes.
[0037] The fiber length and fiber diameter of the single-walled carbon nanotubes contained in the positive electrode active material layer 21b are not particularly limited. The fiber length of the single-walled carbon nanotubes is, for example, 5 μm or more and 1000 μm or less. The fiber diameter of the carbon nanotubes is, for example, 1 nm or more and 20 nm or less. The fiber length and fiber diameter of the single-walled carbon nanotubes can be measured using an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0038] The content of single-walled carbon nanotubes in the positive electrode active material layer 21b is, for example, 0.01 mass% or more, and preferably 0.03 mass% or more. The content of single-walled carbon nanotubes in the positive electrode active material layer 21b is, for example, 0.1 mass% or less, and preferably 0.07 mass% or less. The mass ratio of the specific positive electrode binder to the single-walled carbon nanotubes in the positive electrode active material layer 21b (specific positive electrode binder / single-walled carbon nanotubes) is, for example, 8 to 200.
[0039] (Other ingredients) The positive electrode active material layer 21b may contain other components other than the positive electrode active material, the specific positive electrode binder, and the single-walled carbon nanotubes as necessary. Examples of the other components include other binders, dispersants, conductive assistants, electrolytes (polymer matrices, ion-conductive polymers, electrolyte solutions, etc.), and electrolyte supporting salts (lithium salts) for enhancing ion conductivity. The types and contents of the other components are not particularly limited, and conventionally known knowledge about lithium ion secondary batteries may be appropriately referred to.
[0040] Examples of the dispersant include sodium salt of carboxymethylcellulose and ammonium salt of carboxymethylcellulose. The content of the dispersant in the positive electrode active material layer 21b is, for example, 2.0 mass% or less, preferably 1.0 mass% or less, and more preferably 0.5 mass% or less. The content of the dispersant in the positive electrode active material layer 21b is, for example, 0.3 mass% or more.
[0041] Examples of the conductive additive include acetylene black, carbon black, and graphite. The content of the conductive additive in the positive electrode active material layer 21b is, for example, an amount such that the total amount of the conductive additive and the single-walled carbon nanotubes is 1.0 mass% or less, preferably 0.5 mass% or less, and more preferably 0.1 mass% or less.
[0042] <Manufacturing method of positive electrode> Next, a method for producing the positive electrode 21 will be described. The method for manufacturing the positive electrode 21 includes a coating step of coating the positive electrode mixture onto the positive electrode current collector 21a, and a drying step of drying the positive electrode mixture coated on the positive electrode current collector 21a.
[0043] The positive electrode mixture is a mixture that becomes the positive electrode active material layer 21b by solidification. The positive electrode mixture is, for example, a slurry. The positive electrode mixture contains a positive electrode active material, a specific positive electrode binder, single-walled carbon nanotubes, and an aqueous solvent, and may contain other components as necessary. The positive electrode active material, the specific positive electrode binder, the single-walled carbon nanotubes, and other components contained in the positive electrode mixture are the same as those described in the above positive electrode active material layer section.
[0044] The aqueous solvent is water or a mixed solvent of water and an organic solvent. The aqueous solvent is preferably a solvent in which the mass ratio of water is 50 to 100 mass %. The aqueous solvent is mixed into the positive electrode mixture so that the solid ratio of the positive electrode mixture is, for example, 60 mass % or more and 80 mass % or less.
[0045] The coating step is a step of forming a coating layer of the positive electrode composite by coating the first surface 21a1 of the positive electrode current collector 21a with the positive electrode composite. Examples of methods for coating the positive electrode composite include a roll method, a die coating method, a reverse roll method, a doctor blade method, a knife method, a gravure method, a dip method, and a squeeze method. The positive electrode composite may be continuously or intermittently applied to the first surface 21a1 of the positive electrode current collector 21a. The thickness of the coating layer of the positive electrode composite is such that the basis weight of the finally obtained positive electrode active material layer 21b is 50 mg / cm. 2 The length and width of the coating layer of the positive electrode mixture are appropriately set according to the size of the lithium ion secondary battery.
[0046] The drying step is a step of removing the aqueous solvent and solidifying the coating layer formed on the positive electrode current collector 21a by drying the coating layer. The coating layer solidified through the drying step becomes the positive electrode active material layer 21b. Examples of methods for drying the coating layer include natural drying, low-temperature air, hot air, vacuum, infrared rays, far-infrared rays, electron beams, and microwaves. Two or more of these drying methods may be combined. The drying temperature is, for example, 20°C or higher and 120°C or lower, and preferably 40°C or higher and 100°C or lower.
[0047] Furthermore, in order to increase the electrode density, a compression step of compressing the positive electrode active material layer 21b may be performed after the drying step. This compression step corresponds to the above-mentioned pressing process. Examples of a method for compressing the positive electrode active material layer 21b include a die pressing method and a calendar pressing method. The pressing pressure is, for example, 0.1 t / cm. 2 More than 10t / cm 2 less than 0.5t / cm 2 More than 5.0t / cm 2 The following is the result.
[0048] When the compression step is performed, the thickness of the positive electrode active material layer 21b subjected to the compression step, i.e., the thickness of the positive electrode active material layer 21b before the press treatment, is, for example, 227 μm or more, and preferably 273 μm or more. The thickness of the positive electrode active material layer 21b before the press treatment is, for example, 600 μm or less, and preferably 533 μm or less. The density of the positive electrode active material layer 21b before the press treatment is, for example, 1.5 g / cm 3 More than 2.2g / cm 3 The following is the result.
[0049] A winding step may be performed between each of the above steps and at least once after all the steps have been performed, in which the positive electrode current collector 21a is wound into a roll shape. Also, a drying step may be performed again after the compression step.
[0050] Here, the method for producing a positive electrode includes a bending step of bending the positive electrode current collector 21a on which the positive electrode active material layer 21b is formed after the drying step. The curved state means that at least a part of the positive electrode active material layer 21b is curved to a specific radius of curvature or less, for example, 26 mm or less, or 25.5 mm or less.
[0051] The bending process may be, for example, a winding process in which the positive electrode current collector 21a on which the positive electrode active material layer 21b is formed is wound around a core material, and a bending process in which the positive electrode current collector 21a is curved along the circumferential surface of a cylindrical body. The winding process may be, for example, the winding process described above. The bending process may be, for example, a process in which the positive electrode current collector 21a on which the positive electrode active material layer 21b is formed is conveyed by rollers, in which the positive electrode current collector 21a is curved along the circumferential surface of a cylindrical body such as a guide roller or a tension roller. The bending process may be performed once or multiple times.
[0052] <Electricity storage device> Next, an example of an electricity storage device to which the positive electrode 21 is applied will be described. The power storage device to which the positive electrode 21 is applied is, for example, a lithium ion secondary battery used as a battery for various vehicles such as a forklift, a hybrid car, and an electric car.
[0053] 2, the energy storage device 10 includes a cell stack 30 (laminate) in which a plurality of energy storage cells 20 are stacked in a stacking direction. Hereinafter, the stacking direction of the plurality of energy storage cells 20 will be simply referred to as the stacking direction. Each energy storage cell 20 includes a positive electrode 21, a negative electrode 22, a separator 23, and a spacer 24.
[0054] The positive electrode 21 includes a positive electrode collector 21a and a positive electrode active material layer 21b provided on a first surface 21a1 of the positive electrode collector 21a. In a plan view, the positive electrode active material layer 21b is formed in the center of the first surface 21a1 of the positive electrode collector 21a. In a plan view, the peripheral portion of the first surface 21a1 of the positive electrode collector 21a is a positive electrode uncoated portion 21c where the positive electrode active material layer 21b is not provided. The positive electrode uncoated portion 21c is disposed so as to surround the periphery of the positive electrode active material layer 21b in a plan view.
[0055] The negative electrode 22 includes a negative electrode current collector 22a and a negative electrode active material layer 22b provided on a first surface 22a1 of the negative electrode current collector 22a. In a plan view, the negative electrode active material layer 22b is formed in the center of the first surface 22a1 of the negative electrode current collector 22a. In a plan view, the peripheral portion of the first surface 22a1 of the negative electrode current collector 22a is a negative electrode uncoated portion 22c where the negative electrode active material layer 22b is not provided. The negative electrode uncoated portion 22c is disposed so as to surround the periphery of the negative electrode active material layer 22b in a plan view.
[0056] The positive electrode 21 and the negative electrode 22 are arranged such that the positive electrode active material layer 21b and the negative electrode active material layer 22b face each other in the stacking direction. That is, the facing direction of the positive electrode 21 and the negative electrode 22 coincides with the stacking direction. The negative electrode active material layer 22b is formed to have the same size as the positive electrode active material layer 21b, or is formed to be one size larger than the positive electrode active material layer 21b. When the negative electrode active material layer 22b is formed to be one size larger than the positive electrode active material layer 21b, the entire formation region of the positive electrode active material layer 21b is located within the formation region of the negative electrode active material layer 22b in a plan view.
[0057] The positive electrode current collector 21a has a second surface 21a2 opposite to the first surface 21a1. The positive electrode 21 is an electrode having a monopolar structure in which neither the positive electrode active material layer 21b nor the negative electrode active material layer 22b is formed on the second surface 21a2 of the positive electrode current collector 21a. The negative electrode current collector 22a has a second surface 22a2 opposite to the first surface 22a1. The negative electrode 22 is an electrode having a monopolar structure in which neither the positive electrode active material layer 21b nor the negative electrode active material layer 22b is formed on the second surface 22a2 of the negative electrode current collector 22a.
[0058] The separator 23 is disposed between the positive electrode 21 and the negative electrode 22 and is a member that allows lithium ions to pass through while isolating the positive electrode 21 and the negative electrode 22 to prevent a short circuit caused by contact between the two electrodes.
[0059] The separator 23 is, for example, a porous sheet or nonwoven fabric containing a polymer that absorbs and retains an electrolyte. Examples of materials constituting the separator 23 include polyolefins such as polypropylene and polyethylene, and polyesters. The separator 23 may have a single-layer structure or a multi-layer structure. The multi-layer structure may include, for example, an adhesive layer, a ceramic layer as a heat-resistant layer, and the like.
[0060] The spacer 24 is disposed between the first surface 21a1 of the positive electrode collector 21a of the positive electrode 21 and the first surface 22a1 of the negative electrode collector 22a of the negative electrode 22, and on the outer periphery side of the positive electrode active material layer 21b and the negative electrode active material layer 22b, and is bonded to both the positive electrode collector 21a and the negative electrode collector 22a. The spacer 24 maintains a gap between the positive electrode collector 21a and the negative electrode collector 22a to prevent a short circuit between the collectors and to liquid-tightly seal the space between the collectors.
[0061] The spacer 24 extends along the peripheral edges of the positive electrode current collector 21a and the negative electrode current collector 22a in a plan view, and is formed in a frame shape surrounding the periphery of the positive electrode current collector 21a and the negative electrode current collector 22a. The spacer 24 is disposed between the positive electrode uncoated portion 21c of the first surface 21a1 of the positive electrode current collector 21a and the negative electrode uncoated portion 22c of the first surface 22a1 of the negative electrode current collector 22a.
[0062] Examples of materials constituting the spacer 24 include various resin materials such as polyethylene (PE), modified polyethylene (modified PE), polystyrene (PS), polypropylene (PP), modified polypropylene (modified PP), ABS resin, and AS resin.
[0063] An enclosed space S is formed inside the energy storage cell 20 and is surrounded by a frame-shaped spacer 24, a positive electrode 21, and a negative electrode 22. A separator 23 and an electrolyte are contained in the enclosed space S. The peripheral portion of the separator 23 is embedded in the spacer 24.
[0064] The electrolyte is, for example, a liquid electrolyte. For example, the liquid electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, the electrolyte salt is LiClO 4 , LiAsF 6 , LiPF 6 , LiBF 4 , LiCF 3 SO 3 , LiN(FSO 2 ) 2 , LiN(CF 3 SO 2 ) 2 As the non-aqueous solvent, known solvents such as cyclic carbonates, cyclic esters, chain carbonates, chain esters, ethers, etc. may be used. Two or more of these known solvent materials may be used in combination.
[0065] The spacer 24 can prevent the electrolyte contained in the sealed space S from leaking out to the outside by sealing the sealed space S between the positive electrode 21 and the negative electrode 22. The spacer 24 can also prevent moisture from entering the sealed space S from the outside of the electricity storage device 10. Furthermore, the spacer 24 can prevent gas generated from the positive electrode 21 or the negative electrode 22 due to, for example, a charge / discharge reaction or the like from leaking out to the outside of the electricity storage device 10.
[0066] The cell stack 30 has a structure in which a plurality of storage cells 20 are stacked such that the second surface 21a2 of the positive electrode current collector 21a and the second surface 22a2 of the negative electrode current collector 22a are in contact with each other. In this way, the plurality of storage cells 20 constituting the cell stack 30 are connected in series.
[0067] Here, in the cell stack 30, two storage cells 20 adjacent to each other in the stacking direction form a pseudo bipolar electrode 25 in which the positive electrode current collector 21a and the negative electrode current collector 22a in contact with each other are regarded as one current collector. The pseudo bipolar electrode 25 includes a current collector having a structure in which the positive electrode current collector 21a and the negative electrode current collector 22a are stacked, a positive electrode active material layer 21b formed on one surface of the current collector, and a negative electrode active material layer 22b formed on the other surface.
[0068] The energy storage device 10 includes a pair of current conductors, consisting of a positive electrode current conductor plate 40 and a negative electrode current conductor plate 50, disposed on either side of the cell stack 30 in the stacking direction of the cell stack 30. The positive electrode current conductor plate 40 and the negative electrode current conductor plate 50 are each made of a material having excellent electrical conductivity.
[0069] The positive electrode current-carrying plate 40 is electrically connected to the second surface 21a2 of the positive electrode current collector 21a of the positive electrode 21 arranged at the outermost position at one end in the stacking direction. The negative electrode current-carrying plate 50 is electrically connected to the second surface 22a2 of the negative electrode current collector 22a of the negative electrode 22 arranged at the outermost position at the other end in the stacking direction. The electricity storage device 10 is charged and discharged through terminals provided on the positive electrode current-carrying plate 40 and the negative electrode current-carrying plate 50, respectively.
[0070] Next, the operation and effects of the first embodiment will be described. (1-1) The positive electrode 21 for the electricity storage device includes a positive electrode current collector 21a having a first surface 21a1, and a positive electrode active material layer 21b formed on the first surface 21a1 of the positive electrode current collector 21a. The positive electrode active material layer 21b contains a positive electrode active material capable of absorbing and releasing charge carriers. The basis weight of the positive electrode active material layer 21b is 50 mg / cm 2 and the content of the positive electrode active material in the positive electrode active material layer 21b is 97 mass % or more. The positive electrode active material layer 21b contains a water-based binder (specific positive electrode binder) having a glass transition temperature of less than 7° C., and single-walled carbon nanotubes.
[0071] According to the above configuration, the positive electrode active material layer 21b has high flexibility due to cooperation between the aqueous binder contained in the positive electrode active material layer 21b, which has a glass transition temperature of less than 7° C., and the single-walled carbon nanotubes. This makes it possible to suppress cracking of the positive electrode active material layer 21b that occurs when a bending load is applied to the positive electrode active material layer 21b in the bending step or the like in the manufacturing stage of the positive electrode 21. As a result, it is possible to suppress detachment of the positive electrode active material layer 21b from the positive electrode current collector 21a when a process in which a load is applied to the positive electrode 21 is performed during the manufacturing of an electricity storage device using the positive electrode 21.
[0072] (1-2) The aqueous binder (specific positive electrode binder) contains a compound having an aromatic ring. In this case, the aromatic rings of the aqueous binder and the single-walled carbon nanotubes are easily moved together due to the π-π interaction between them, and therefore the positive electrode active material layer 21b has higher flexibility.
[0073] (1-3) The electricity storage device 10 includes a positive electrode 21, a negative electrode 22, a separator 23, and a spacer 24. The positive electrode 21 has a positive electrode active material layer 21b provided on a first surface 21a1 of a positive electrode collector 21a. The negative electrode 22 has a negative electrode active material layer 22b provided on a first surface 22a1 of a negative electrode collector 22a, and is disposed such that the negative electrode active material layer 22b faces the positive electrode active material layer 21b of the positive electrode 21. The separator 23 is disposed between the positive electrode active material layer 21b and the negative electrode active material layer 22b. The spacer 24 is disposed between the first surfaces 21a1, 22a1 of the positive electrode collector 21a and the negative electrode collector 22a, and is bonded to the first surfaces 21a1, 22a1 of the positive electrode collector 21a and the negative electrode collector 22a.
[0074] When manufacturing the electricity storage device having the above configuration, it is necessary to perform a process of stacking the positive electrode 21 and the negative electrode 22 via the separator 23 and the spacer 24, and a process of bonding the positive electrode 21 and the spacer 24. Therefore, compared with the case of manufacturing a general prismatic battery, a laminated battery, and a cylindrical battery, a load is applied to the positive electrode active material layer 21b of the positive electrode 21 many times, and as a result, the positive electrode active material layer 21b is more likely to detach from the positive electrode current collector 21a during manufacturing. Therefore, when the positive electrode 21 of this embodiment is applied to the electricity storage device 10 having the above configuration, the effect of suppressing the detachment of the positive electrode active material layer 21b from the positive electrode current collector 21a can be more significantly obtained.
[0075] Second Embodiment Next, a second embodiment embodied in a bipolar electrode will be described. The bipolar electrode can be used, for example, in place of the pseudo bipolar electrode 25 in the power storage device 10 described above.
[0076] 3, the bipolar electrode 100 includes a bipolar current collector 101, a positive electrode active material layer 102, and a negative electrode active material layer 103. In this embodiment, the bipolar current collector 101 corresponds to the current collector described in the claims.
[0077] The bipolar current collector 101 is a chemically inactive electrical conductor for continuing to pass current through the positive electrode active material layer 102 and the negative electrode active material layer 103 during discharging or charging of the power storage device. The bipolar current collector 101 has a shape that can be bent and deformed into a curved state, for example, a foil shape. The bipolar current collector 101 has a first surface 101a and a second surface 101b facing the opposite side to the first surface 101a. The first surface 101a and the second surface 101b are surfaces perpendicular to the thickness direction of the bipolar current collector 101.
[0078] The bipolar current collector 101 is a laminate formed by integrally joining a positive electrode current collector 104 and a negative electrode current collector 105 in the thickness direction. A first surface 101a of the bipolar current collector 101 is formed by the positive electrode current collector 104. A second surface 101b of the bipolar current collector 101 is formed by the negative electrode current collector 105. A positive electrode active material layer 102 is provided on the first surface 101a of the bipolar current collector 101. A negative electrode active material layer 103 is provided on the second surface 101b of the bipolar current collector 101.
[0079] [Positive electrode current collector and positive electrode active material layer] The positive electrode current collector 104 is a chemically inactive electrical conductor for continuing to pass a current through the positive electrode active material layer 102 during discharging or charging of the lithium ion secondary battery. Each component of the positive electrode current collector 104 is similar to that of the positive electrode current collector 21a of the first embodiment. Each component of the positive electrode active material layer 102 is similar to that of the positive electrode active material layer 21b of the first embodiment.
[0080] [Negative electrode current collector] The negative electrode current collector 105 is a chemically inactive electrical conductor for continuing to pass a current through the negative electrode active material layer 103 during discharging or charging of the lithium ion secondary battery. The thickness of the negative electrode current collector 105 is, for example, 4 μm or more, and preferably 6 μm or more. The thickness of the negative electrode current collector 105 is, for example, 20 μm or less, and preferably 10 μm or less.
[0081] An example of the negative electrode current collector 105 is a copper current collector whose surface serving as the second surface 101b is made of copper. The copper current collector may be a simple substance entirely made of copper, or a complex having a portion made of copper and a portion made of a material other than copper. An example of the simple substance is copper foil. An example of the complex is a multilayer structure in which the layer constituting the second surface 101b is a copper layer, or a substrate whose surface including the second surface 101b is covered with a copper film.
[0082] The negative electrode current collector 105 may be formed of a material other than copper. Examples of materials other than copper include metal materials, conductive resin materials, and conductive inorganic materials. Examples of the metal materials include aluminum, nickel, titanium, and stainless steel (for example, SUS304, SUS316, SUS301, SUS304, etc., as specified in JIS G 4305:2015). Examples of the conductive resin materials include resins in which a conductive filler is added to a conductive polymer material or a non-conductive polymer material as necessary.
[0083] An example of a preferred combination of the positive electrode current collector 104 and the negative electrode current collector 105 constituting the bipolar current collector 101 is a case in which the positive electrode current collector 104 is made of aluminum foil and the negative electrode current collector 105 is made of copper foil. Examples of the bipolar current collector 101 include a current collector in which aluminum foils are bonded together, a current collector in which aluminum foil and copper foil are bonded together, and a current collector in which the surface of aluminum foil is plated with copper.
[0084] [Negative electrode active material layer] The weight of the negative electrode active material layer 103 is, for example, 20 mg / cm2 or more, preferably 30 mg / cm 2 That's all. The weight per unit area is 20 mg / cm 2 By doing so, it is possible to effectively increase the energy density of a lithium ion secondary battery using the bipolar electrode 100. Furthermore, the increase in the energy density of the lithium ion secondary battery improves battery characteristics such as battery capacity and long-term output.
[0085] The weight of the negative electrode active material layer 103 is, for example, 50 mg / cm 2 or less, preferably 40 mg / cm 2 The above weight is 50mg / cm 2 When the negative electrode active material layer 103 has a smaller thickness, the height of the lithium ion secondary battery using the bipolar electrode 100 can be reduced. 2 That's all.
[0086] The thickness of the negative electrode active material layer 103 is, for example, 125 μm or more and 556 μm or less. The density of the negative electrode active material layer 103 is, for example, 0.9 g / cm 3 More than 1.6g / cm 3 The negative electrode active material layer 103 may be one that has been subjected to a press treatment. The pressed negative electrode active material layer 103 may have a thickness of, for example, 125 μm or more, and preferably 187 μm or more. The pressed negative electrode active material layer 103 may have a thickness of, for example, 500 μm or less, and preferably 400 μm or less. The pressed negative electrode active material layer 103 may have a density of, for example, 1.0 g / cm 3 More than 1.6g / cm 3 The following is the result.
[0087] The negative electrode active material layer 103 contains a negative electrode active material, a specific negative electrode binder, and single-walled carbon nanotubes. (Negative electrode active material) The negative electrode active material can absorb and release charge carriers such as lithium ions. The negative electrode active material is graphite. Examples of graphite include natural graphite, artificial graphite, hard carbon (hardly graphitizable carbon), and soft carbon (easily graphitizable carbon). Examples of artificial graphite include highly oriented graphite and mesocarbon microbeads. One type of graphite may be used alone, or multiple types may be used in combination.
[0088] It is preferable that the graphite contains a large amount of graphite structure. For example, the graphite has a G / D ratio determined by Raman spectroscopy of 2 or more, preferably 3 or more. The G / D ratio of the graphite is, for example, 5 or less, preferably 4 or less. The G / D ratio is measured by Raman spectroscopy using an argon ion laser beam at a wavelength of 1570 to 1620 cm. -1 The intensities of the peaks in the range of IA and 1350-1370 cm -1 When the intensity of the peak existing in the range is IB, the ratio IB / IA is expressed. When graphite containing a large amount of graphite structure is used, π-π interaction occurs between the single-walled carbon nanotubes in the negative electrode active material layer 103. This allows a specific negative electrode binder and the single-walled carbon nanotubes to work together when a bending load is applied to the negative electrode active material layer 103.
[0089] The average particle size (D50) of the graphite is, for example, 10 μm or more and 20 μm or less. The average particle size (D50) of the graphite can be measured using a laser diffraction particle size analyzer. The content of the negative electrode active material in the negative electrode active material layer 103 is, for example, 90 mass % or more, preferably 95 mass % or more, and more preferably 96.5 mass % or more. The content of the negative electrode active material in the negative electrode active material layer 103 is, for example, 98 mass % or less, and preferably 97.5 mass % or less. By making the content of the negative electrode active material 90 mass % or more, it is possible to effectively increase the energy density of the lithium ion secondary battery using the bipolar electrode 100. Furthermore, by increasing the energy density of the lithium ion secondary battery, battery characteristics such as battery capacity and long-term output are improved.
[0090] (Specific negative electrode binder) The specific negative electrode binder is an aqueous binder having a glass transition temperature of less than 7° C. The aqueous binder is a binder that is used by being mixed with the negative electrode active material in a state where it is dispersed or dissolved in an aqueous solvent.
[0091] The glass transition temperature of the specific negative electrode binder is less than 7° C., preferably not more than 0° C., and more preferably not more than −5° C. When the specific negative electrode binder has a glass transition temperature of less than 7° C., the flexibility of the negative electrode active material layer 103 is improved.
[0092] Examples of the specific negative electrode binder include various resin materials, for example, fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluorine rubber, thermoplastic resins such as polypropylene and polyethylene, imide resins such as polyimide and polyamideimide, alkoxysilyl group-containing resins, acrylic resins such as poly(meth)acrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, alginates such as sodium alginate and ammonium alginate, water-soluble cellulose ester crosslinked bodies, and starch-acrylic acid graft polymers. The specific negative electrode binder contained in the negative electrode active material layer 103 may be one type or two or more types.
[0093] The glass transition temperature of a specific negative electrode binder can be adjusted by changing the degree of polymerization of the resin material and the ratio of the constituent units that make up the resin material. For example, in the case of styrene-butadiene rubber, the glass transition temperature can be adjusted by changing the ratio of the constituent units styrene and butadiene. Specifically, the glass transition temperature of styrene-butadiene rubber can be lowered by increasing the ratio of butadiene to styrene.
[0094] The specific negative electrode binder is preferably a compound having an aromatic ring. In this case, in the negative electrode active material layer 103, π-π interactions occur between the aromatic ring of the specific negative electrode binder and the single-walled carbon nanotube, and between the aromatic ring of the specific negative electrode binder and the graphite. This allows the specific negative electrode binder and the single-walled carbon nanotube to work together, and the specific negative electrode binder and the graphite to work together, when a bending load is applied to the negative electrode active material layer 103. Examples of compounds having an aromatic ring include styrene-butadiene rubber.
[0095] The content of the specific negative electrode binder in the negative electrode active material layer 103 is, for example, 2.0 mass % or more, and preferably 2.3 mass % or more. By increasing the content of the specific negative electrode binder, the binding property in the negative electrode active material layer 103 can be increased. The content of the specific negative electrode binder in the negative electrode active material layer 103 is, for example, 4.0 mass % or less, and preferably 3.0 mass % or less. The specific negative electrode binder is a component that does not contribute to charging and discharging in the negative electrode active material layer 103. By reducing the content of the component that does not contribute to charging and discharging, the energy density of the lithium ion secondary battery can be increased. And, by increasing the energy density of the lithium ion secondary battery, the battery characteristics such as the battery capacity and long-term output can be improved.
[0096] (single-walled carbon nanotubes) In the negative electrode active material layer 103, the single-walled carbon nanotubes may be present in a state of being bundled with, for example, about several tens of tubes.
[0097] The fiber length and fiber diameter of the single-walled carbon nanotubes contained in the negative electrode active material layer 103 are not particularly limited. The fiber length of the single-walled carbon nanotubes is, for example, 5 μm or more and 1000 μm or less. The fiber diameter of the carbon nanotubes is, for example, 1 nm or more and 10 μm or less. The fiber length and fiber diameter of the single-walled carbon nanotubes can be measured using an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0098] The content of the single-walled carbon nanotubes in the negative electrode active material layer 103 is, for example, 0.001 mass% or more, and preferably 0.005 mass% or more. The content of the single-walled carbon nanotubes in the negative electrode active material layer 103 is, for example, 0.02 mass% or less, and preferably 0.015 mass% or less. In addition, the mass ratio of the specific negative electrode binder to the single-walled carbon nanotubes in the negative electrode active material layer 103 (specific negative electrode binder / single-walled carbon nanotubes) is, for example, 100 or more and 4000 or less.
[0099] (Other ingredients) The negative electrode active material layer 103 may contain other components other than the negative electrode active material, the specific negative electrode binder, and the single-walled carbon nanotubes as necessary. Examples of the other components include other binders, dispersants, conductive assistants, electrolytes (polymer matrices, ion-conductive polymers, electrolyte solutions, etc.), and electrolyte supporting salts (lithium salts) for enhancing ion conductivity. The types and contents of the other components are not particularly limited, and conventionally known knowledge about lithium ion secondary batteries may be appropriately referred to.
[0100] Examples of the dispersant include sodium salt of carboxymethylcellulose and ammonium salt of carboxymethylcellulose. The content of the dispersant in the negative electrode active material layer 103 is, for example, 1.0 mass% or less, and preferably 0.5 mass% or less. The content of the dispersant in the negative electrode active material layer 103 is, for example, 0.3 mass% or more.
[0101] Examples of the conductive additive include acetylene black, carbon black, and graphite. The content of the conductive additive in the negative electrode active material layer 103 is, for example, an amount such that the total amount of the conductive additive and the single-walled carbon nanotubes is 0.5% by mass or less, and preferably 0.1% by mass or less.
[0102] <Bipolar electrode manufacturing method> Next, a method for manufacturing the bipolar electrode 100 will be described. The method for manufacturing the bipolar electrode 100 includes a positive electrode forming step and a negative electrode forming step.
[0103] The positive electrode forming process includes a positive electrode coating process in which a positive electrode composite is coated on the first surface 101a of the bipolar current collector 101, and a positive electrode drying process in which the positive electrode composite coated on the bipolar current collector 101 is dried. The positive electrode coating process and the positive electrode drying process are similar to the coating process and the drying process described in the above-mentioned positive electrode manufacturing method, except that the bipolar current collector 101 for the bipolar electrode 100 is used instead of the positive electrode current collector 21a.
[0104] The negative electrode forming step includes a negative electrode coating step of coating a negative electrode mixture on second surface 101b of bipolar current collector 101, and a negative electrode drying step of drying the negative electrode mixture coated on bipolar current collector 101.
[0105] The negative electrode mixture is a mixture that becomes the negative electrode active material layer 103 by solidification. The negative electrode mixture is, for example, a slurry. The negative electrode mixture contains a negative electrode active material, a specific negative electrode binder, single-walled carbon nanotubes, and an aqueous solvent, and may contain other components as necessary. The negative electrode active material, the specific negative electrode binder, the single-walled carbon nanotubes, and other components contained in the negative electrode mixture are the same as those described in the negative electrode active material layer section above.
[0106] The aqueous solvent is water or a mixed solvent of water and an organic solvent. The aqueous solvent is preferably a solvent in which the mass ratio of water is 50 to 100 mass %. The aqueous solvent is mixed into the negative electrode mixture so that the solid ratio of the negative electrode mixture is, for example, 50 mass % or more and 65 mass % or less.
[0107] The negative electrode coating step and the negative electrode drying step are the same as the positive electrode coating step and the positive electrode drying step, except that a negative electrode mixture is used instead of a positive electrode mixture. Note that the thickness of the coating layer formed in the negative electrode coating step is such that the weight of the finally obtained negative electrode active material layer 103 is 20 mg / cm. 2 Adjust the thickness to be equal to or greater than this.
[0108] The order of performing the positive electrode forming step and the negative electrode forming step is arbitrary. For example, the negative electrode forming step may be performed after the positive electrode forming step, or the positive electrode forming step may be performed after the negative electrode forming step. Also, a part or all of the positive electrode forming step and the negative electrode forming step may be performed simultaneously. For example, after the application of the positive electrode composite material to the first surface 101a of the bipolar current collector 101 and the application of the negative electrode composite material to the first surface 101a of the bipolar current collector 101 are performed simultaneously, the coating layer of the positive electrode composite material and the coating layer of the negative electrode composite material may be dried simultaneously.
[0109] Furthermore, in order to increase the electrode density, after only one of the positive electrode drying step and the negative electrode drying step or after both of them have been performed, a compression step may be performed to compress one or both of the positive electrode active material layer 102 and the negative electrode active material layer 103. The compression step is the same as the compression step described in the above-mentioned method for producing a positive electrode.
[0110] When the compression step is performed on the negative electrode active material layer 103, the thickness of the negative electrode active material layer 103 to be subjected to the compression step, i.e., the thickness of the negative electrode active material layer 103 before the press treatment, is, for example, 167 μm or more, and preferably 250 μm or more. The thickness of the negative electrode active material layer 103 before the press treatment is, for example, 556 μm or less, and preferably 444 μm or less. The density of the negative electrode active material layer 103 before the press treatment is, for example, 0.9 g / cm 3 More than 1.2g / cm 3 The following is the result.
[0111] Between each of the above steps, or at least at some timing after all steps have been performed, a winding step may be performed to wind the bipolar current collector 101 into a roll shape. In addition, after the compression step, one or both of the positive electrode drying step and the negative electrode drying step may be performed again.
[0112] Here, the method for manufacturing the bipolar electrode 100 includes a bending step of bending the bipolar current collector 101 on which the positive electrode active material layer 102 is formed after the positive electrode drying step. The bending step is the same as the bending step described in the method for manufacturing the positive electrode. Note that, when the negative electrode forming step is performed after the positive electrode forming step, the bending step may be performed during the negative electrode forming step.
[0113] The bipolar electrode 100 of the second embodiment also provides the same advantages as those (1-1) to (1-3) described for the positive electrode 21 of the first embodiment. Furthermore, according to the second embodiment, the following further advantages are provided.
[0114] (2-1) The bipolar electrode 100 includes a bipolar current collector 101 having a first surface 101a and a second surface 101b facing the opposite side to the first surface 101a. A positive electrode active material layer 102 is formed on the first surface 101a of the bipolar current collector 101, and a negative electrode active material layer 103 is formed on the second surface 101b. The configuration of the positive electrode active material layer 102 is similar to that of the positive electrode active material layer 21b of the first embodiment.
[0115] In the bipolar electrode 100, it is necessary to form an active material layer on both the first surface 101a and the second surface 101b of the bipolar current collector 101. Therefore, compared with a monopolar electrode in which an electrode is formed only on one surface of the current collector, the manufacturing process of the bipolar electrode 100 requires more bending steps in which a bending load is applied to the positive electrode active material layer 102, and as a result, the positive electrode active material layer 102 is more likely to crack. Therefore, when the positive electrode active material layer 102 of the bipolar electrode 100 is configured to include a water-based binder having a glass transition temperature of less than 7°C and single-walled carbon nanotubes, the effect of suppressing cracking of the positive electrode active material layer 102 can be more significantly obtained.
[0116] (2-2) The weight of the negative electrode active material layer 103 is 20 mg / cm 2 The negative electrode active material layer 103 contains a negative electrode active material, a negative electrode binder having a glass transition temperature of less than 7° C., and single-walled carbon nanotubes.
[0117] According to the above-mentioned configuration, the negative electrode active material layer 103 has high flexibility due to the cooperation between the aqueous binder having a glass transition temperature of less than 7° C. contained therein and the single-walled carbon nanotubes. This makes it possible to suppress cracking of the negative electrode active material layer 103 that occurs when a bending load is applied to the negative electrode active material layer 103. As a result, it is also possible to suppress detachment of the negative electrode active material layer 103 from the bipolar current collector 101 when a process in which a load is applied to the bipolar electrode 100 is performed during the manufacture of the electricity storage device.
[0118] This embodiment can be modified as follows: This embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs. The configuration of the negative electrode active material layer 103 of the bipolar electrode 100 is not limited to that in the above embodiment, and any known configuration of a negative electrode active material layer used in the negative electrode of a power storage device can be used.
[0119] The planar shapes of the positive electrode current collector 21a and the positive electrode active material layer 21b are not particularly limited and may be, for example, a polygonal shape such as a rectangle, a circular shape, or an elliptical shape. The planar shapes of the negative electrode current collector 22a and the negative electrode active material layer 22b are not particularly limited and may be, for example, a polygonal shape such as a rectangle, a circular shape, or an elliptical shape.
[0120] A positive electrode active material layer 21b may be provided on the second surface 21a2 of the positive electrode current collector 21a. There is no particular limitation on the number of power storage cells 20 constituting the power storage device 10. For example, the number of power storage cells 20 constituting the power storage device 10 may be one. EXAMPLES
[0121] Hereinafter, a more specific embodiment of the above embodiment will be described. <Preparation of positive electrode> LiFePO with carbon coating layer 4Granulated polystyrene (LFP), styrene-butadiene rubber (SBR), carbon nanotubes (CNT), and sodium carboxymethyl cellulose (CMC) were mixed in the proportions shown in Tables 1 and 2, and water was added to this mixture to prepare a positive electrode mixture with a solid content of 75 mass %.
[0122] The type of carbon nanotube used is shown in the "CNT type" column of Tables 1 and 2. The amount of carbon nanotube blended in each example was adjusted so that the electrode resistance was approximately the same. The "SBR Tg (°C)" column of Tables 1 and 2 shows the glass transition temperature of the styrene-butadiene rubber used. The above glass transition temperature is the glass transition onset temperature in a DSC curve measured using DSC in accordance with JIS K 7121 (1987), except that the heating rate was 10°C / min.
[0123] An aluminum foil with a thickness of 30 μm was prepared as a current collector. The positive electrode mixture was applied to one surface of the current collector in the form of a film using a doctor blade method. The applied positive electrode mixture was heated at 50° C. to dry and solidify the positive electrode mixture, resulting in a positive electrode mixture having a coating weight of 50 mg / cm on the current collector. 2 or 75 mg / cm 2 Positive electrodes of Examples 1 to 3, Comparative Examples 1 to 3, and Reference Examples 1 and 2 in which the above positive electrode active material layers were formed were produced.
[0124] <Bending test> The positive electrode of each example was cut to 5 cm x 10 cm and used as a test sample. The test sample was wrapped around half of the outer periphery of a cylinder with a diameter of 20 mm, with the side on which the positive electrode active material layer was formed facing outward, and the surface condition of the positive electrode active material layer was then visually evaluated. The results are shown in Tables 1 and 2. The evaluation criteria were as follows:
[0125] "◯": No cracks were found on the surface of the positive electrode active material layer. "X": Cracks were present on the surface of the positive electrode active material layer.
[0126] [Table 1]
[0127] [Table 2] Examples 1 to 3 are examples in which the positive electrode active material layer contains an aqueous binder having a glass transition temperature of less than 7°C and single-walled carbon nanotubes. No cracks were observed in the positive electrode active material layers of Examples 1 to 3. On the other hand, cracks were observed in the positive electrode active material layer of Comparative Example 1, in which an aqueous binder having a glass transition temperature of 7°C was used instead of an aqueous binder having a glass transition temperature of less than 7°C. Furthermore, cracks were observed in the positive electrode active material layer of Comparative Example 2, in which multi-walled carbon nanotubes were used instead of single-walled carbon nanotubes, and in the positive electrode active material layer of Comparative Example 3, in which no carbon nanotubes were included. From these results, it can be seen that the effect of suppressing cracks in the positive electrode active material layer in Examples 1 to 3 is not the sole effect of the aqueous binder having a glass transition temperature of less than 7°C or the sole effect of the single-walled carbon nanotubes, but is an effect obtained by the cooperation of both components.
[0128] Although detailed experimental data is omitted, a similar bending test was carried out using a cylinder having a diameter of 13 mm instead of the cylinder having a diameter of 20 mm for Examples 1 to 3. As a result, no cracks were found in the positive electrode active material layers of Examples 1 to 3.
[0129] Reference Examples 1 and 2 are examples in which a water-based binder with a glass transition temperature of 7° C. is used and no carbon nanotubes are contained, and the basis weight of the positive electrode active material layer is different from each other. 2 In Reference Example 1, no cracks were found in the positive electrode active material layer, whereas the coating weight was 75 mg / cm 2In Reference Example 2, cracks were confirmed in the positive electrode active material layer. Thus, even when an aqueous binder having a glass transition temperature of 7° C. or higher is used and when single-walled carbon nanotubes are not contained, when the basis weight of the positive electrode active material layer is small, cracks do not occur in the positive electrode active material layer. Therefore, it can be seen that the cracks in the positive electrode active material layer caused by the application of bending stress are a phenomenon that appears when the basis weight of the positive electrode active material layer is increased. Therefore, the effect of suppressing cracks in the positive electrode active material layer by using an aqueous binder having a glass transition temperature of less than 7° C. and single-walled carbon nanotubes in combination is an effect that cannot be predicted from the configuration in which the basis weight of the positive electrode active material layer is small.
[0130] <Bipolar electrode fabrication and bending test> LiFePO with carbon coating layer 4 Granulated polystyrene (LFP), styrene-butadiene rubber (SBR), single-walled carbon nanotubes (CNT), and sodium carboxymethyl cellulose (CMC) were mixed in the proportions shown in Table 3, and water was added to this mixture to prepare a positive electrode mixture with a solid content of 75 mass%.
[0131] Graphite with a G / D ratio of 3.4, styrene-butadiene rubber (SBR), single-walled carbon nanotubes (CNT), and carboxymethylcellulose sodium salt (CMC) were mixed in the proportions shown in Table 3, and water was added to this mixture to prepare a negative electrode mixture with a solid content ratio of 56 mass%.
[0132] A 30 μm thick aluminum foil with an 8 μm thick copper foil laminated on one surface of the current collector was prepared. A film of the positive electrode mixture was applied to the aluminum foil side of the current collector using a doctor blade method. The applied positive electrode mixture was heated at 50° C. to dry and solidify the positive electrode mixture, resulting in a coating weight of 75 mg / cm on the current collector. 2Then, the negative electrode mixture was applied in the form of a film to the surface of the current collector on the copper foil side by a doctor blade method. The applied negative electrode mixture was heated at 50°C to dry and solidify the negative electrode mixture, forming a positive electrode active material layer of 37.8 mg / cm on the current collector. 2 Thus, a bipolar electrode having a positive electrode active material layer and a negative electrode active material layer was produced.
[0133] [Table 3] Two samples were used as test samples: one cut into 5cm x 10cm from the prepared bipolar electrode, and the other cut into 120cm x 150cm from the prepared bipolar electrode. The test sample was wrapped around half of the outer circumference of a cylinder with a diameter of 50mm, with the side on which the positive electrode active material layer was formed facing outward, and the surface condition of the positive electrode active material layer and the surface condition of the negative electrode active material layer were visually evaluated. As a result, no cracks were found in either the positive electrode active material layer or the negative electrode active material layer in either test sample.
[0134] Next, the technical ideas that can be understood from the above embodiment and modified examples will be described below. [Aspect 1] A current collector having a first surface, and a positive electrode active material layer formed on the first surface of the current collector, The positive electrode active material layer contains a positive electrode active material capable of absorbing and releasing charge carriers, The positive electrode active material layer has a coating weight of 50 mg / cm 2 and the content of the positive electrode active material in the positive electrode active material layer is 97 mass% or more, The positive electrode active material layer is an aqueous binder having a glass transition temperature of less than 7°C; A positive electrode for an electricity storage device, comprising: a single-walled carbon nanotube.
[0135] [Aspect 2] 2. The positive electrode for an electricity storage device according to embodiment 1, wherein the aqueous binder contains a compound having an aromatic ring. [Aspect 3] 3. The positive electrode for an electricity storage device according to embodiment 2, wherein the compound having an aromatic ring is styrene-butadiene rubber.
[0136] [Aspect 4] the current collector has a second surface facing opposite the first surface; The positive electrode for a power storage device according to any one of aspects 1 to 3, which is a bipolar electrode in which the positive electrode active material layer is formed on the first surface of the current collector and the negative electrode active material layer is formed on the second surface of the current collector.
[0137] [Aspect 5] The content of the aqueous binder in the positive electrode active material layer is 0.8% by mass or more and 2.0% by mass or less, A positive electrode for an electricity storage device according to any one of aspects 1 to 4, wherein the content of the single-walled carbon nanotubes in the positive electrode active material layer is from 0.01% by mass to 0.1% by mass.
[0138] [Aspect 6] A positive electrode for an electricity storage device according to any one of aspects 1 to 5, wherein the positive electrode active material has a carbon coating on a surface thereof.
[0139] [Aspect 7] A positive electrode for an electricity storage device according to any one of aspects 1 to 6, wherein the positive electrode active material is a polyanionic compound having an olivine structure.
[0140] [Aspect 8] a positive electrode having a positive electrode active material layer provided on a first surface of a positive electrode current collector; a negative electrode having a negative electrode active material layer provided on a first surface of a negative electrode current collector, the negative electrode active material layer being disposed so as to face the positive electrode active material layer of the positive electrode; a separator disposed between the positive electrode active material layer and the negative electrode active material layer; a spacer disposed between first surfaces of the positive electrode current collector and the negative electrode current collector and bonded to the first surfaces of the positive electrode current collector and the negative electrode current collector, The positive electrode is a positive electrode for use in the power storage device according to any one of aspects 1 to 7. [Explanation of symbols]
[0141] 21...Positive electrode 21a...Positive electrode current collector 21a1…1st surface 21b...Cathode active material layer 100...Bipolar electrode 101...Bipolar current collector 101a...first surface 101b…Second surface 102...Cathode active material layer 103...Negative electrode active material layer 104...Positive electrode current collector 105...Negative electrode current collector
Claims
1. a current collector having a first surface; and a positive electrode active material layer formed on the first surface of the current collector; The positive electrode active material layer contains a positive electrode active material capable of absorbing and releasing charge carriers, The weight of the positive electrode active material layer is 50 mg / cm 2 and the content of the positive electrode active material in the positive electrode active material layer is 97 mass% or more, The positive electrode active material layer is an aqueous binder having a glass transition temperature of less than 7°C; A positive electrode for an electricity storage device, comprising: a single-walled carbon nanotube.
2. The positive electrode for an electricity storage device according to claim 1 , wherein the aqueous binder contains a compound having an aromatic ring.
3. 3. The positive electrode for an electricity storage device according to claim 2, wherein the compound having an aromatic ring is a styrene-butadiene rubber.
4. the current collector has a second surface facing opposite the first surface; 2. The positive electrode for an electricity storage device according to claim 1, which is a bipolar electrode in which the positive electrode active material layer is formed on the first surface of the current collector and the negative electrode active material layer is formed on the second surface of the current collector.
5. a positive electrode having a positive electrode active material layer provided on a first surface of a positive electrode current collector; a negative electrode having a negative electrode active material layer provided on a first surface of a negative electrode current collector, the negative electrode active material layer being disposed so as to face the positive electrode active material layer of the positive electrode; a separator disposed between the positive electrode active material layer and the negative electrode active material layer; a spacer disposed between first surfaces of the positive electrode current collector and the negative electrode current collector and bonded to the first surfaces of the positive electrode current collector and the negative electrode current collector, The positive electrode is a positive electrode for the power storage device according to any one of claims 1 to 4.
Citation Information
Patent Citations
Lithium-ion secondary battery
JP2013004241A
Nonaqueous electrolyte secondary battery
JP2016106346A
Positive electrode and lithium battery including positive electrode
JP2020035746A
Cathode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
JP2021150051A
Method for manufacturing slurry for positive electrode of secondary battery
JP2022155939A